Stability of pace and turn parameters of elite long-distance swimmers - Morais, J.E. (2018)
This study aimed to assess the stability of the performance, pace and turn parameters of elite long-distance male swimmers during an 800 m freestyle race. The sample was composed by 38 male swimmers, participating in the 800 m event at the 2016 LEN European Aquatic Championships (long course meter). The performance, and a set of pace and turn parameters were analyzed. A customized software was used to perform each race analysis. Swimmers spent 64.05 ± 0.50% and 35.95 ± 0.49% of the final race time in the clean swim and turns, respectively. In the pace parameters, the clean swim was the only one that did not differ between the first and second half of the race (1.63 ± 0.05 vs 1.62 ± 0.05 m·s−1), and in the turn parameters, the water break distance was also similar (5.13 ± 1.17 vs 5.06 ± 0.98 m). A significant and moderate-strong variation was verified for the performance (total race lap effect: p < 0.001, η2 = 0.62), and a significant and moderate variation for the pace parameters (total race: p < 0.001, 0.15 ≤ η2 ≤ 0.33), and for the turn parameters (total race: p < 0.01, 0.15 ≤ η2 ≤ 0.33). Present data (pace and turn variation) shows that elite long-distance male swimmers do not maintain a similar pattern during an 800 m freestyle race. Future research is need to understand if this lack of pace and turn stability is the best way to enhance the performance, or if swimmers should be advised to control their pace and turn. Nevertheless, coaches are advised to help swimmers with feedback about their pace (i.e., controlling the intermediate 30 m) and turn performances (i.e., controlling the 5 m in and 15 m out), leading to a positive effect in their final race time.